Genetic and palaeo-climatic evidence for widespread persistence of the coastal tree species Eucalyptus gomphocephala (Myrtaceae) during the Last Glacial Maximum - Nevill, Paul; Bradbury, D.; Williams, A.; Tomlinson, S.; Krauss, S. (2014)
Background and Aims: Few phylogeographic studies have been undertaken of species confined to narrow, linear coastal systems where past sea level and geomorphological changes may have had a profound effect on species population sizes and distributions. In this study, a phylogeographic analysis was conducted of Eucalyptus gomphocephala (tuart), a tree species restricted to a 400 × 10 km band of coastal sand-plain in south west Australia. Here, there is little known about the response of coastal vegetation to glacial/interglacial climate change, and a test was made as to whether this species was likely to have persisted widely through the Last Glacial Maximum (LGM), or conforms to a post-LGM dispersal model of recovery from few refugia. Methods: The genetic structure over the entire range of tuart was assessed using seven nuclear (21 populations; n = 595) and four chloroplast (24 populations; n = 238) microsatellite markers designed for eucalypt species. Correlative palaeodistribution modelling was also conducted based on five climatic variables, within two LGM models.Key Results: The chloroplast markers generated six haplotypes, which were strongly geographically structured (GST = 0·86 and RST = 0·75). Nuclear microsatellite diversity was high (overall mean HE 0·75) and uniformly distributed (FST = 0·05), with a strong pattern of isolation by distance (r2 = 0·362, P = 0·001). Distribution models of E. gomphocephala during the LGM showed a wide distribution that extended at least 30 km westward from the current distribution to the palaeo-coastline. Conclusions: The chloroplast and nuclear data suggest wide persistence of E. gomphocephala during the LGM. Palaeodistribution modelling supports the conclusions drawn from genetic data and indicates a widespread westward shift of E. gomphocephala onto the exposed continental shelf during the LGM. This study highlights the importance of the inclusion of complementary, non-genetic data (information on geomorphology and palaeoclimate) to interpret phylogeographic patterns.